2022
DOI: 10.1530/ec-21-0600
|View full text |Cite
|
Sign up to set email alerts
|

Untreated thyroid autoantibody-negative SCH increases the risk of spontaneous abortions

Abstract: Background: Numerous studies have found that subclinical hypothyroidism (SCH) may increase the adverse pregnancy outcomes; however, the benefit of levothyroxine (LT4) treatment remains controversial.Therefore, the primary goal of this study was to investigate the correlation between thyroid autoantibodies negative-SCH with or without LT4 treatment and adverse pregnancy outcomes. Methods: 1344 women involved the study according the inclusion and exclusion criteria. Assays for thyroid stimulating hormone (TSH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…SCH is also associated with alterations in lipid profiles, although the extent and impact of these changes are still under investigation (as shown in Figure 2 ). Observational studies have shown that SCH patients in early pregnancy have TC, TG, HDL-c, and LDL-c levels than normal pregnant women [ 18 ]. In the second and third trimesters, SCH patients continued to exhibit higher TC, TG, and LDL-c levels, but there was no significant difference in HDL-c levels [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCH is also associated with alterations in lipid profiles, although the extent and impact of these changes are still under investigation (as shown in Figure 2 ). Observational studies have shown that SCH patients in early pregnancy have TC, TG, HDL-c, and LDL-c levels than normal pregnant women [ 18 ]. In the second and third trimesters, SCH patients continued to exhibit higher TC, TG, and LDL-c levels, but there was no significant difference in HDL-c levels [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For pregnant patients with hypothyroidism, clinical guidelines suggested that L-T4 replacement therapy should be given promptly to mitigate the risk of dyslipidemia and adverse neonatal outcomes [ 14 ]. Although observational studies have demonstrated that dyslipidemia has also been observed in SCH pregnant women [ 18 24 ]. A large cohort study involving 20,365 participants demonstrated that L-T4 treatment significantly reduced TC and LDL-c levels in SCH patients during the first trimester [ 91 ].…”
Section: Introductionmentioning
confidence: 99%
“…On account of the relevant studies being negative or conflicting (12,18,19), national colleges of obstetrics do not consider subclinical thyroid dysfunction to be a relevant entity (20, 21). Nevertheless, increasing numbers of pregnant women are having thyroid treatments (22) presumably in part on account of guidelines (23)(24)(25) and some positive trials concerning both associations of subclinical hypothyroidism with pregnancy outcomes and treatment of the thyroid state (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%